Reflexive Pasts. Cultural Pragmatics, Identity Formation and the Roles of Social and Collective Memory - Mori, Luca (Italian Sociological Review, 2011)
Drawing on some theoretical stimuli provided by cultural sociology, the article will show how, when it comes to discussing the identity-creating function of memory, focusing the analysis on the relationship between representations of the past and the process of identity building is not enough. In addition, it is necessary to evaluate whether it is appropriate to include the consciousness (that here is assumed to be increasingly widespread) of the socially constructed nature of each identity in the concept of memory. In this case, memory would play an ambivalent role regarding identity. On the one hand, memory would represent a vital resource for its construction and retention, while on the other it could constitute an element making actors aware of the artificiality of their selves, therefore ending up by playing a destabilizing role. Some consequences of this way of conceiving memory are discussed with regards to the general process of forgetting and the so-called ‘ethics of memory’.